The protective effects of saxagliptin against lipopolysaccharide (LPS)-induced inflammation and damage in human dental pulp cells - Xinxing Guo; Jing Chen (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Bacteria play a pivotal role in the pathological initiation and progression of pulpitis. Lipopolysaccharide (LPS) is recognized as a major component of the outer wall of Gram-negative bacteria. Saxagliptin, a potent inhibitor of dipeptidyl peptidase-4 (DPP-4), has been licensed for the treatment of type 2 diabetes. In this study, we aimed to evaluate the protective effects of saxagliptin against LPS-induced intracellular insults in human dental pulp cells (HDPCs). We found that DPP-4 is expressed in HDPCs. Interestingly, the expression of DPP-4 was increased in response to LPS treatment. We also found that saxagliptin ameliorated LPS-induced production of ROS and reduction of glutathione (GSH). Additionally, saxagliptin prevented LPS-induced mitochondrial dysfunction by increasing the levels of mitochondrial membrane potential (MMP) and the production of adenosine triphosphate (ATP). Importantly, saxagliptin ameliorated LPS-induced reduction of cell viability and lactate dehydrogenase (LDH) release. Our results indicate that saxagliptin significantly inhibited LPS-induced expression and secretions of tumour necrosis factor alpha (TNF-α), interleukin (IL)-1β and IL-6 in HDPCs. Mechanistically, we found that saxagliptin inhibited the phosphorylation of p38 and the activation of NF-κB. Our findings suggest that saxagliptin might have a potential therapeutic capacity for the treatment of pulpitis through mitigating inflammatory signalling in dental pulp cells.